Evaluation of antimicrobial effect of photodynamic therapy (PDT) on root canal microflora in patients with diseases of the pulp and periodontal tissues (Эндодонтия Today)
Research is aimed at studying the antimicrobial efficacy of photodynamic therapy in treatment patients with pulpitis and periodontitis. Light-emitting-diode lamp «Fotosan» with wavelength 625-635nm was used as light source. Toluidine blue was used as photosensitizer. 73 specimens of root canal content before and after PDT were tested. The current study results prove the antimicrobial efficacy of PDT in endodontic treatment.